Kedudukan Wakaf Tunai Dalam Hukum Islam Dan Peraturan Perundang-Undangan Indonesia - Laudza Hulwatun Azizah; Khairunisa Khairunisa; Vichi Novalia; Maulina Maulina; Ali Murtadho Emzaed (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Background Cash waqf is an innovation in waqf asset management that provides flexibility and greater economic potential in the context of Islamic law. In Islamic law, cash waqf is defined as the handing over of cash for social and religious purposes, which is then managed to produce benefits for society. In Indonesia, regulations regarding cash waqf have been regulated in statutory regulations, including Law no. 41 of 2004 concerning Waqf, which provides a legal framework for more effective management of waqf. However, challenges in implementing cash waqf still exist, including outreach to the community, lack of understanding of this concept, and management mechanisms that are not yet optimal.